FROM ONTOLOGICAL SUBJECT OF SOCIOLOGY JUSTIFICATION TO DISCLOSURE OF ITS SOCIAL FUNCTIONS - V. Y. Fetisov (Дискурс, 2016)
The lack of interaction between the Russian society and social knowledge necessary for the development of each of them is stated. Sociology is analyzed from these positions as an important component of social knowledge, its state of crisis, which manifests itself in inability to perform social functions. A different compared to the existing interpretation of the definition of the sociology subject is suggested, and on this basis, adjustments are made concerning its content, epistemological and social functions are revealed. Justification of the latter increases interest to sociology, contributes to its demand on the part of the society.